Strain elastography for detecting advanced Fontan-associated liver disease: a retrospective study - Koji Imoto; Takeshi Goya; Yuki Azuma; Tomonobu Hioki; Tomomi Aoyagi; Hazumu Nagata; Akiko Nishizaki; Takamori Kakino; Ayako Ishikita; Kenichiro Yamamura; Ichiro Sakamoto; Masatake Tanaka; et al. (BMC Gastroenterology)
Abstract Background The Fontan procedure has improved the prognosis of patients with a functional single ventricle; however, late complications—including Fontan-associated liver disease (FALD)—have surfaced as clinical concerns. FALD with signs of portal hypertension has been defined as advanced FALD (aFALD) due to its poor prognosis. Recently, noninvasive tests (NITs) have been found to predict liver fibrosis in FALD. Liver stiffness measurement excluding strain elastography (SE) was affected by hepatic congestion; however, to our knowledge, not many studies have evaluated the SE-derived Liver Fibrosis Index (LFI). This study aimed to determine the efficacy of NITs, especially LFI, for discriminating aFALD. Methods In this retrospective study, 46 Japanese patients with FALD were included and classified into the aFALD (33 patients; 22 males and 11 females; median age: 28.0 years) and non-aFALD (13 patients; seven males and six females; median age: 22.0 years) groups based on the presence/absence of signs of portal hypertension. Results The platelet count, FIB-4 index, Forns index, and LFI differed significantly between the two groups and demonstrated moderate accuracy for discriminating aFALD. The shear wave velocity (Vs) measured by Shear Wave Elastography (SWE) did not differ significantly between the two groups. The cut-off value of platelet counts below 185 × 103/μL had 78.8% sensitivity and 92.3% specificity. While 25/26 (96.2%) of the patients with FALD who had platelet counts below 185 × 103/μL were aFALD, 8/20 (40.0%) of the patients with FALD who had platelet counts above below 185 × 103/μL were also aFALD, indicating the need for additional markers. In the patients with FALD who had platelet counts above 185 × 103/μL, only SE indicated moderate diagnostic accuracy, and the LFI cut-off value of 2.21 had 100% sensitivity and 75.0% specificity. Conclusions Using a two-step approach, discriminating aFALD with platelet counts below 185 × 103/μL by platelets alone, and for those with higher platelet counts, requiring LFI > 2.21 could discriminate aFALD with high accuracy. Early detection of aFALD and early intervention, including testing for aFALD, may lead to an improved prognosis of aFALD.